USE DIFFERENT LANGUAGES OF KNOWLEDGE REPRESENTATION AS A FACTOR OF MATHEMATICS EDUCATION HUMANIZATION - Sagan, О.В. (Journal of Information Technologies in Education (ITE), 2015)
A lot of educational projects get no further development primarily due to the lack of competent academic staff. It is not only the professional knowledge, abilities and skills, but also the ability to perceive educational innovations and ability to implement them. With regard to the mathematics education the most urgent is the problem of humanization, which appears in the ratio of scientific knowledge, national and cultural revival, issues of values and new type of education content. The problem of humanizing of mathematical education isexamined in the article, in particular in the field of training ofpedagogical personnels. As for the serve of mathematicalmaterial the language of formal logic, that is regulated by thesecond alarm system, is used, it results in the deficit ofinformation of the first alarm system, that is responsible forperception, imagination, supervision, experience. Logical isthe use of such methods serves of information, thatmaximally use both сигнальних systems of man. It issuggested one of directions of upgrading of educating tomathematics of future teachers except the traditionallanguage of formal logic to use the alternative languages ofserve of material : language of semantic networks, languageof the system of frames, language of productional.